Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/nano10081578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper Dopants on the Magnetic Property of Lightly Cu-Doped ZnO Nanocrystals

Abstract: To explore the origin of magnetism, the effect of light Cu-doping on ferromagnetic and photoluminescence properties of ZnO nanocrystals was investigated. These Cu-doped ZnO nanocrystals were prepared using a facile solution method. The Cu2+ and Cu+ ions were incorporated into Zn sites, as revealed by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). At the Cu concentration of 0.25 at.%, the saturated magnetization reached the maximum and then decreased with increasing Cu concentration. With i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 49 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…19 Wang et al have experimentally shown that the Cu ions can enhance the long-range ferromagnetic ordering at an ultralow concentration via the indirect double exchange mechanism, but antiferromagnetic "Cu + -V 0 -Cu 2+ " coupling may also be generated, as a superexchange mechanism, even at a very low Cu-doping concentration. 20 One of the key objectives of this work was to determine quantitively the amount of Cu inserted into the ZnO host matrix. Some researchers have noticed that the hexacoordinated ionic radius of Cu 2+ (0.73 Å) is slightly smaller than the one of Zn 2+ (0.74 Å), they have argued that this could solve the determination of the copper content by scrutinizing its effect on the lattice parameters that should decrease upon doping with Cu.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Wang et al have experimentally shown that the Cu ions can enhance the long-range ferromagnetic ordering at an ultralow concentration via the indirect double exchange mechanism, but antiferromagnetic "Cu + -V 0 -Cu 2+ " coupling may also be generated, as a superexchange mechanism, even at a very low Cu-doping concentration. 20 One of the key objectives of this work was to determine quantitively the amount of Cu inserted into the ZnO host matrix. Some researchers have noticed that the hexacoordinated ionic radius of Cu 2+ (0.73 Å) is slightly smaller than the one of Zn 2+ (0.74 Å), they have argued that this could solve the determination of the copper content by scrutinizing its effect on the lattice parameters that should decrease upon doping with Cu.…”
Section: Introductionmentioning
confidence: 99%
“…19 Wang et al have experimentally shown that the Cu ions can enhance the long-range ferromagnetic ordering at an ultralow concentration via the indirect double exchange mechanism, but antiferromagnetic “Cu + –V 0 –Cu 2+ ” coupling may also be generated, as a super-exchange mechanism, even at a very low Cu-doping concentration. 20…”
Section: Introductionmentioning
confidence: 99%